(untitled) (Revista Brasileira de Iniciação Científica, 2022)
Autistic Spectrum Disorder (ASD) is a condition whose severity and chronicity imply a greater demand for care. In view of this, the family is called upon to mobilize and adapt to the needs of the autistic child, which requires many changes in the family dynamics. In this sense, this article aims to analyze the impact of the presence of a member with ASD in the family, in order to understand which aspects of family dynamics contribute or not to the child’s development. For that, a bibliographical research was carried out, in order to analyze the production on the subject. The results reveal that the child with ASD demands more attention and mobilization from the family. Consequently, there is an increase in the level of stress, physical and emotional overload of family members, especially the mother. It is concluded that there is a need for interaction between family and school so that both can work together to promote the healthy development of children with ASD.